Streptococcus bovis Bacteremia in Neonates in a Predominantly Hispanic Population - Alvarez, Alicia; Jia, Yi; Garcia, Cesar J.; Rosas-Blum, Eduardo D.; Boman, Darius; Zuckerman, Marc J. (Frontiers in Pediatrics, 2015)
Background: Streptococcus bovis bacteremia has been associated with gastrointestinal diseases, especially colon cancer, neoplastic colon polyps and other malignancies of the GI tract in adults. Sporadic cases of S. bovis disease have also been reported in neonates and young infants. Although uncommon, S. bovis infection can cause fulminant neonatal sepsis and meningitis. Objectives: We report a series of pediatric patients with S. bovis bacteremia in a county hospital in a United States - Mexico border city in order to examine the demographic and clinical associations. Methods: We characterized the demographic and clinical features in all pediatric patients with blood cultures positive for S. bovis at University Medical Center in El Paso, Texas between January 2000 and December 2010. Hospital records were systematically reviewed by using a standardized protocol. Results: A total of 7 episodes of S. bovis bacteremia were documented in 7 pediatric patients (4 female and 3 male). Mean age was 1.2 days (range 1-3 days), all were Hispanic, average birth weight (3.25 kg). Mode of delivery was spontaneous vaginal delivery (5) and Caesarian section (2). All of our patients developed early (< 1 week) onset disease and presented with signs of respiratory distress. Five out of 7 babies presented with abdominal distention and diarrhea. Six had clinical evidence of sepsis at presentation. Respiratory distress was the most common manifestation of sepsis (7). Aspiration pneumonia was diagnosed in 2 of them. Most patients were treated with a combination of antibiotics (6), either ampicillin and gentamicin or ampicillin and cefotaxime, and one with ampicillin alone. None of the pediatric patients had endoscopy and none of them died. Conclusions: S. bovis is considered an uncommon pathogen in the newborn, but can be associated with substantial morbidity and mortality if not identified and treated early. Physicians should be alert to the less common presentation of neonatal bacteremia due to S. bovis.